2017
DOI: 10.3389/fimmu.2017.00950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depleting Therapeutic Monoclonal Antibodies on the Host Adaptive Immunity: A Bonus or a Malus?

Abstract: Clinical responses to anti-tumor monoclonal antibody (mAb) treatment have been regarded for many years only as a consequence of the ability of mAbs to destroy tumor cells by innate immune effector mechanisms. More recently, it has also been shown that anti-tumor antibodies can induce a long-lasting anti-tumor adaptive immunity, likely responsible for durable clinical responses, a phenomenon that has been termed the vaccinal effect of antibodies. However, some of these anti-tumor antibodies are directed against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…Thus, we have performed a longitudinal prospective study on peripheral blood from a small-sized cohort of similarly treated FL patients with high tumor burden, each receiving the same R-CHOP induction treatment followed by a maintenance treatment for most patients (25/33). Our study focused on the analysis of T-cell compartments, as preclinical data in mouse models as well as clinical investigations have suggested that T cells may play a major role in the control of tumor progression and in responses to antibody-based treatments 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have performed a longitudinal prospective study on peripheral blood from a small-sized cohort of similarly treated FL patients with high tumor burden, each receiving the same R-CHOP induction treatment followed by a maintenance treatment for most patients (25/33). Our study focused on the analysis of T-cell compartments, as preclinical data in mouse models as well as clinical investigations have suggested that T cells may play a major role in the control of tumor progression and in responses to antibody-based treatments 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that this effect is caused by the induction of an adaptive immune memory response via T- and B-lymphocytes (Fig. 3) [64]. Exosomes may interfere with this therapeutic adaptive immune response by affecting T- and B- lymphocyte function as well as antigen presentation [65].…”
Section: Exosomes and Tumor Immune Escape Mechanismmentioning
confidence: 99%
“…Cancer immunotherapies and drugs modulating the immune system are emerging as important treatment modalities for hematological and solid tumors 46,47 Monocytes and T cell subsets formed two separate clusters. B and NK cells had similar drug response patterns.…”
Section: Innate Drug Sensitivities In Cell Subsets Are Retained In Thmentioning
confidence: 99%